Reasons for a basic income program: poverty, economic crisis or end-of-work? A literature review - Rocha, Rafael de Acypreste Monteiro (Informe Econômico (UFPI), 2023)
Interest in basic income tends to grow in times of crisis, especially with current high rates of unemployment, poverty and the impact caused by the COVID-19 pandemic. This article aims to evaluete the characteristics of the debate on basis income for every citizen in the last twelve years. There are three mains reasons for basic income: 1) problems caused by poverty; 2) constant crises of the capitalism system; 3) massive destruction of jobs by automation. It is concluded that there is no consensus on the design of such a program, neither on its relationship with social welfare policies nor on its population coverage.